3D mesoscale analysis of concrete containing defect damages during different freeze-thaw cycles. (5th December 2022) - Miao, Haibin; Guo, Chao; Lu, Zhengran; Chen, Zhihua
Highlights: A 3D mesoscale model of concrete damage under freeze-thaw cycles was presented. Damage of different numbers of freeze-thaw cycles was described by Weibull distribution equations. Python script process can set up a concrete coupled temp-displacement mesoscale platform on ABAQUS. Abstract: The damage process of concrete containing air pore and aggregate gradation defects under freeze-thaw (FT) cycles was parametrically studied by an ABAQUS coupled thermo-mechanical mesoscale numerical analyses platform. It was a stochastic finite element model (SFEM) developed by Python script program. The effectiveness of mesoscale model was verified by comparing 96 concrete samples divided to 4 groups with air pore and aggregate defects exposed to 0 to 90 FT cycles. The damage function of concrete for FT cycles was described by Weibull distribution equations. The analyses showed that air pore defects had a significant impact on concrete mechanical characteristics under FT cycles. When FT cycle number ( n ) reached 90, the strength loss of specimens with no defect was about 37.5%. When air pore content was 5% with non-uniform grading of aggregate, the strength loss of specimen was 61.6%. This showed that FT cycle damage effect on concrete was obvious which was more prominent for higher values of n .